Differences in the force system delivered by different beta-titanium wires in elaborate designs - Martins, Renato Parsekian [UNESP] (2015)
Objective: Evaluation of the force system produced by four brands of β-Ti wires bent into an elaborate design. Methods: A total of 40 T-loop springs (TLS) hand-bent from 0.017 x 0.025-in β-Ti were randomly divided into four groups according to wire brand: TMA™ (G1), BETA FLEXY™ (G2), BETA III WIRE™ (G3) and BETA CNA™ (G4). Forces and moments were recorded by a moment transducer, coupled to a digital extensometer indicator adapted to a testing machine, every 0.5 mm of deactivation from 5 mm of the initial activation. The moment-to-force (MF) ratio, the overlapping of the vertical extensions of the TLSs and the load-deflection (LD) ratio were also calculated. To complement the results, the Young’s module (YM) of each wire was determined by the slope of the load-deflection graph of a tensile test. The surface chemical composition was also evaluated by an energy dispersive X-ray fluorescence spectrometer. Results: All groups, except for G2, produced similar force levels initially. G3 produced the highest LD rates and G1 and G4 had similar amounts of overlap of the vertical extensions of the TLSs in “neutral position”. G1 and G3 delivered the highest levels of moments, and G2 and G3 produced the highest MF ratios. β-Ti wires from G3 produced the highest YM and all groups showed similar composition, except for G2. Conclusion: The four beta-titanium wires analyzed produced different force systems when used in a more elaborate design due to the fact that each wire responds differently to bends.